2001
DOI: 10.1182/blood.v98.1.100
|View full text |Cite
|
Sign up to set email alerts
|

Novel structurally altered P2X1 receptor is preferentially activated by adenosine diphosphate in platelets and megakaryocytic cells

Abstract: Experimental and clinical data suggest the presence of multiple types of adenosine diphosphate (ADP) receptors, one coupled to ligand-gated cation channels (P 2X ) and others coupled to G-proteincoupled (P 2Y ) receptors. This report identifies cDNA for a structurally altered P 2X1 -like receptor in megakaryocytic cell lines (Dami and CMK 11-5) and platelets that, when transfected into nonresponsive 1321 cells, confers a specific sensitivity to ADP with the pharmacologic rank order of ADP > > ATP > > > ␣,␤-met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 45 publications
2
27
0
Order By: Relevance
“…Some recent studies have been able to demonstrate P2X 1 -mediated amplification of the responses to both collagen and P2Y receptors [29,30]. Our findings of high P2X 1 expression in platelets together with reports of a patient with bleeding disorder with a dominant-negative mutation in the platelet P2X 1 receptor [31,32], suggests that a synergistic role for this receptor in platelet aggregation merits investigation in more physiological assays.…”
Section: Discussionsupporting
confidence: 69%
“…Some recent studies have been able to demonstrate P2X 1 -mediated amplification of the responses to both collagen and P2Y receptors [29,30]. Our findings of high P2X 1 expression in platelets together with reports of a patient with bleeding disorder with a dominant-negative mutation in the platelet P2X 1 receptor [31,32], suggests that a synergistic role for this receptor in platelet aggregation merits investigation in more physiological assays.…”
Section: Discussionsupporting
confidence: 69%
“…However, the molecular characterization of the guinea pig P2X 1 receptor is required before further conclusions can be drawn. The recent report of phenotypically altered rat P2X 1 receptors generated by alternative splicing (Greco et al, 2001) further complicates the comparison of native and recombinant P2X receptor responses. We are left with the conclusion that heteromeric assemblies of rP2X 1 and rP2X 2 subunits would best explain the unique pH sensitivity and unusual pharmacological activity of agonists at P2X 1 -like responses.…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper on the characterization of the platelet receptor drew attention to the dangers of using impure commercial preparations of nucleotides (296), showing that actions ascribed to ADP were not observed after it was purified. On the other hand, Greco et al (156) found a splice variant of the P2X 1 receptor to be abundant in human platelets. This variant lacks 17 amino acids at the beginning of exon 6, and the difference appears to have a large effect on the agonist selectivity of the receptor.…”
Section: Plateletsmentioning
confidence: 99%
“…vI3). Finally, a spliced form of the hP2X 1 receptor that lacks most of exon 6 (including the conserved glycosylation site Asn-184) has been found in platelets and megakaryocyte cell line (156). When expressed in fibroblasts and studied by calcium imaging, this receptor showed a much reduced sensitivity to ␣␤meATP.…”
Section: Agonistsmentioning
confidence: 99%